Emerging biological threat - Berencsi, György; Khan, Akbar S.; Haloužka, Jiři (NATO science series. Life and behavioural sciences, 2005)
Summarizes projects aiming to detect risks of biological toxins, superantigens and the modeling of their effects. This volume presents the potential risks, detection and prevention of chronic and zoonotic infections in addition to interaction of human pathogens affecting biological risks. It also includes experimental vaccines and therapeutics.